2017
DOI: 10.1097/igc.0000000000001065
|View full text |Cite
|
Sign up to set email alerts
|

The First Nationwide Multicenter Prevalence Study of Germline BRCA1 and BRCA2 Mutations in Chinese Ovarian Cancer Patients

Abstract: Germline BRCA1/2 mutations is common in Chinese ovarian cancer patients. This study implies that all ovarian patients should be tested for gBRCAm status regardless of family history and histopathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
62
4

Year Published

2018
2018
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(86 citation statements)
references
References 45 publications
20
62
4
Order By: Relevance
“…This BRCA2 predominance was previously observed in prostate cancer patients 23 . However, the majority of gBRCAm in ovarian cancer are predominantly composed of BRCA1 mutations (172/235, 73.2%) 2 . In prostate cancer, patients with germline BRCA2 mutations showed elevated global genomic instability and harbored unique mutations that were rarely or not yet been reported in sporadic localized prostate cancer 24,25 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This BRCA2 predominance was previously observed in prostate cancer patients 23 . However, the majority of gBRCAm in ovarian cancer are predominantly composed of BRCA1 mutations (172/235, 73.2%) 2 . In prostate cancer, patients with germline BRCA2 mutations showed elevated global genomic instability and harbored unique mutations that were rarely or not yet been reported in sporadic localized prostate cancer 24,25 .…”
Section: Discussionmentioning
confidence: 99%
“…Approximately, 5% of breast cancer cases and 20%–30% of ovarian cancers are caused by germline alterations in the breast cancer susceptibility type 1 and 2 ( BRCA1 and BRCA2 ) genes 1,2 . Women with germline BRCA mutation ( gBRCAm ) have significantly higher lifetime risk of developing breast, ovarian, tubal, and peritoneal cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Our analysis has shown that this frequency among Chinese OC patients was higher (21.8%) (Figure c). In fact, one large sample size screening (826 patients) indicated that this variant frequency in Chinese OC patients was 28.5% (Wu et al, ). Family history appeared to be a strong risk factor since BRCA1/2 pathogenic variant was found in 41.0% of patients with family history.…”
Section: Resultsmentioning
confidence: 99%
“…The prevalence of germline BRCA1/2 variants shows a large variation across different ethnicities, ranging from 6.5% to 25.0% in BC and from 12.1% to 29% in OC (Han et al, ; Kim et al, ; Robson et al, ; Weitzel et al, ). Due to remarkable advances in next‐generation sequencing (NGS) technologies (Rainville & Rana, ), it is now possible to investigate the prevalence of different BRCA1/2 variants in patients of distinct ethnicities, as well as their clinical significance (Sun et al, ; Wu et al, ). It is known that the homologous recombination repair function can be affected by pathogenic BRCA1/2 variants, which are randomly distributed along with coding and noncoding regions, with no defined hotspots (Weitzel et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In a study of 916 patients with Chinese epithelial ovarian cancer, the incidence of BRCA1/2 mutation was 16.7%, with a BRCA1 mutation rate of 13.1%, BRCA2 mutation rate of 3.9% and concurrent BRCA1 and BRCA2 mutation rate of 0.3% . In another nationwide multicenter study of 826 Chinese patients, the incidence of germline BRCA1/2 mutation was 28.5%, with a BRCA1 mutation rate of 20.8% and BRCA2 mutation rate of 7.6% . The strikingly different prevalences found in previous studies and the deficiency of clinical characteristics calls for further large population‐based studies on this issue.…”
Section: Introductionmentioning
confidence: 98%